Intracranial hemorrhage during pregnancy - A. Zh. Bayalieva; V. R. Davydova; M. Mokhsin; E. Iu. Iupatov (Акушерство, гинекология и репродукция)
Here, we review publications aimed at assessing the prevalence of intracranial hemorrhage, types of hemorrhage in pregnant patients, diagnostic features, as well as the basic principles of treatment used in such cases. There a represented pathologies in pregnant women such as subarachnoid, subdural, extradural hemorrhage, thrombosis of cavernous sinuses, arteriovenous malformations, neoplasms. There are summarized data within the years from 2015 to 2020 retrieved from the search databases PubMed/MEDLINE, Google Scholar, and Web of Science. Based on our study, it was concluded that intracranial hemorrhages during pregnancy most often occur in the third trimester. This is due to several factors: development of preeclampsia, increased blood pressure, coagulopathy, HELLP-syndrome, physiological remodeling of cerebral autoregulation, and concomitant initial pathology of cerebral vessels such as aneurysms and arteriovenous malformations. We also draw special attention to the importance of timely differential diagnostics of hypertensive conditions during preeclampsia and neurosurgical pathology requiring urgent intervention.